Indian legal and constitutional history - Mittal, J. K. (Allahabad, 1984)
Madras is the first and one of the three Presidency towns. Its settle ment arose out of a grant made by the local Raja in 1639 who empowered the Company to erect a fortified factory on a strip of land, to mint money and to govern the village of Madraspatnam, on condition that half the cus toms and revenues of the port should be paid to the Raja. The new trading station was named Fort St. George and an Agent and Council took over its charge in 1641 under the control of Surat Presidency. It acquired the status of Presidency in 1666. The Fort area, inhabited by the English and Euro peans, was later designated as white town and the village area of Madras patnam, inhabited by the natives, as black town. The whole establishment ultimately developed into the modern city of Madras.
Keywords: India-Constitutional history